Immunohistochemical assessment of tumor suppressor gene Wwox in relation to proliferative marker KI67 proteins expression in giant cell lesions of the jaws and giant cell tumor of long bones - Merza, Muna S (Journal of Baghdad College of Dentistry, 2015)
Background: Peripheral giant cell lesion (PGCL) and central giant cell lesion (CGCL) of the jaws have a distinct clinical behavior.Giant cell tumour (GCT) is a benign locally aggressive neoplasm affects the long bones. Both lesions are characterized histologically by multinucleated giant cells in a background of ovoid to spindle-shaped mesenchymal cells. The WW domain-containing oxidoreductase (WWOX) gene is located at 16q23.1–16q23.2, a region that spans the second most common human fragile site, FRA16D, at 16q23.2.The Ki-67 antigen is a nuclear protein that is associated with and may be necessary for cellular proliferation.Ki-67 protein is present during all active phases of the cell cycle (G1, S, G2, and mitosis), but is absent from resting cells (G0). This study aimed to evaluate and compare immunohistochemical expression of tumor suppressor gene (WWOX) and proliferative marker (ki67) in giant cell lesions (GCLs) of the jaws and long bones. Materials and methods: Forty five retrospective paraffin embedded tissue blocks of giant cell lesions of the jaw and long bones were included in this study.Sections were stained immunohistochemically with anti WWOX and anti ki67 monoclonal antibodies. Results: Positive WWOX expression was found in 12 cases (80%), 14cases (93.3%)and12 (80%) of CGCG, PGCG and GCT studied cases respectively, with thehighest strong positive expression observed in PGCG.Positive Ki67 expression was found in 12 cases (80% ), 13cases ( 86.7 % )and10(66.7%) of CGCG,PGCG and GCT studied cases respectively with the high proliferative expression score has been recorded in PGCG .Statistically highly significant difference was found in the Ki67expression among different giant lesion types (p=0.006), whilenon-significant difference was found in WWOX expression. Non-significant correlation was found between expression of WWOXand Ki67 in CGCG, PGCG and GCT studied cases. Conclusions: Similar immunohistochemical expression of WWOX and Ki67 ingiant cell lesions of the jaw and GCT of long boneswith non-significant correlation between them in different studied lesionssuggests that those lesions may be the same disease but with different clinical behavior. Keywords: Wwox, KI67.